2014
DOI: 10.1037/a0036502
|View full text |Cite
|
Sign up to set email alerts
|

Equality for all? White Americans’ willingness to address inequality with Asian and African Americans.

Abstract: White Americans' willingness to engage in dialogues about intergroup commonalities and power inequalities with Asian and African Americans were examined in two experiments. Because Whites perceive that African Americans experience greater discrimination than do Asian Americans, we predicted that they would be more willing to engage in dialogues that would interrogate injustice and inequality with them. We also explored the role of common in-group identity (as Americans) on willingness for dialogue about inequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…We also theorize that Black targets (specifically, Black male targets) may activate prejudice concerns more than Asian American targets of either gender. We make this argument based on the public image of Asian Americans as a “model minority”—that is, an ethnic minority group that has achieved economic and educational success (Kitano & Sue, 1973), seemingly experiences minimal discrimination (Bikmen & Durkin, 2014; Pew Research Center, 2010), and has little need for sympathy, concern, or supportive public policies (Chao, Chiu, & Lee, 2010; Lin, Kwan, Cheung, & Fiske, 2005; Weathers & Truxillo, 2008). Moreover, the content of stereotypes about Asian Americans is positive, as well as negative (Lin et al, 2005), and research suggests that people are less cautious about the expression of positive than negative stereotypes (Kay, Day, Zanna, & Nussbaum, 2013).…”
Section: Studymentioning
confidence: 99%
“…We also theorize that Black targets (specifically, Black male targets) may activate prejudice concerns more than Asian American targets of either gender. We make this argument based on the public image of Asian Americans as a “model minority”—that is, an ethnic minority group that has achieved economic and educational success (Kitano & Sue, 1973), seemingly experiences minimal discrimination (Bikmen & Durkin, 2014; Pew Research Center, 2010), and has little need for sympathy, concern, or supportive public policies (Chao, Chiu, & Lee, 2010; Lin, Kwan, Cheung, & Fiske, 2005; Weathers & Truxillo, 2008). Moreover, the content of stereotypes about Asian Americans is positive, as well as negative (Lin et al, 2005), and research suggests that people are less cautious about the expression of positive than negative stereotypes (Kay, Day, Zanna, & Nussbaum, 2013).…”
Section: Studymentioning
confidence: 99%
“…Notably, we also found that outgroup evaluations made by both majority and minority groups in the two cultural contexts remained high across group status and regardless of direct contact. This finding is possible considering the generally positive attitudes toward higher status groups across various settings (Asbrock, 2010; Cuddy et al, 2009) as well as the current positive views toward Chinese Americans in the U.S. (Bikmen & Durkin, 2014; Maddux et al, 2008) and the post-Reform improvement of attitudes of the Chinese community in Indonesia (Chong, 2015; Setijadi, 2016; Turner & Allen, 2007). Again, this finding suggests potential influence of the dynamic sociopolitical situations on the intergroup relations between two very specific groups in each society (see Liu, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is inconsistent with previous studies in other contexts, which suggests that the direct contact effect tends to be stronger for the majority than the minority group members (Binder et al, 2009; Tropp & Pettigrew, 2005). The finding, however, shows that perhaps the model minority stereotype of the Asian Americans in the country influences the way the majority group members evaluate this particular minority ethnic group (Bikmen & Durkin, 2014; Maddux et al, 2008), which indicates that intergroup relations could be influenced by the specific relationship between two particular ethnic groups in a cultural context (Conley et al, 2016; Liang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During interactions with disadvantaged group members, advantaged group members prefer discussing issues that highlight intergroup commonalities, such as shared hobbies or cultural similarities (Saguy, Dovidio, & Pratto, 2008). This preference is linked to advantaged group members' desire to uphold the status quo and draw attention away from inequalities (Saguy et al, 2008; see also Bikmen & Durkin, 2014;Hammack & Pilecki, 2015). However, as advantaged group members' intentions to challenge the status quo increase, their desire for discussing status differences increases as well (Saguy et al, 2008).…”
Section: Representations Of Group Identitiesmentioning
confidence: 99%